COMPARATIVE ANALYSIS OF THE MORPHOLOGICAL CHARACTERISTICS OF ISKANDARIA KUSCHAKEWITSCHI (HERZENSTEIN, 1890) POPULATIONS OCCURRING IN THE QAMCHIQSOY AND OLTIARIQSOY RIVERS (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
In this study, a comparative analysis of the morphometric characteristics of Iskandaria kuschakewitschi (Herzenstein, 1890) populations distributed in the Qamchiqsoy and Oltiariqsoy rivers of the Fergana Valley was carried out. The study was conducted on the basis of samples collected during 2024–2026, and more than 30 morphometric characters were measured according to standard methodology and evaluated using biostatistical methods. According to the results of Student’s t-test, statistically reliable differences at the 1% significance level were identified in 21 out of the 35 studied morphometric characters, while no significant differences were observed in the remaining 14 characters. The greatest differences were recorded in body length, head length, body depth, fin lengths, and caudal peduncle parameters. In the Oltiariqsoy population, the high values of the coefficient of variation are explained by the ecological variability of the environment, whereas the Qamchiqsoy population is characterized by a relatively stable morphological structure. The obtained results indicate the presence of morphological differentiation between the populations and confirm the important role of hydrological factors in its formation.
Keywords: Iskandaria kuschakewitschi, morphometry, population differentiation, Qamchiqsoy, Oltiariqsoy, Nemacheilidae, hydrological factors, variation